Architecture, body, climate. The pleasure of pursuing change - Mazurek, Weronika (Hybris, 2025)
Does the quest to reduce architectures negative impact on the climate have to involve “designing for discomfort”? In this text, I consider whether a turn toward pleasurable experiences in the realm of everyday life can also be a tool for pursuing change. As I argue, this is possible through meaningful architecture that perpetuates a sense of local identity andoffers a multi-sensory experience. These can affect the well-being and health of a society – aspects that I believe are necessary to address the health of the environment and the planet. I base my reflections on research in the fields of everyday aesthetics and somaesthetics, and demonstrate their practical dimension through the analysis and interpretation of a selected project. The case in question is a house in São Paulo, which serves as an inspiration to look for similar but more generally accessible architectural forms. In the end, the examples described turn out to have not only features that affect multisensory perception and well-being, but use natural materials and can affect a favorable microclimate.